(untitled) (International Journal of Engineering and Computer Science, 2016)
Introduction of adamantine problem for environment is pollution that causes fickleness, instability, hard or disquiet to ecosystem. Now days, there are a number of techniques, which are used for the collection and management of the garbage. Zigbee and GSM technologies are not only latest trends but also one of the best combinations to use in the project. Set of carefully chosen sensors to monitor the status of garbage bin. The smart garbage bin consist sensors namely ultrasonic sensor, gas sensor and moisture sensor. Ultrasonic Sensor is used for detect the garbage level. The ultrasonic sensor is placed inside the garbage bin at lead position, gas sensor will sense the toxic gases and moisture sensor will sense moist in bin then that indication will give to PIC micro-controller. The controller will give indication to the cleaning authority and needs urgent attention. The Pic-micro-controller will indication by sending SMS using GSM technology. These Dustbins are interfaced with the central system showing status of garbage in Dustbin on GUI.